Sociodemographic and reproductive risk factors associated with obesity in a population of brazilian women from the city of Ribeirão Preto: a cross-sectional study - Ênio Luis Damaso; Heloisa Bettiol; Viviane Cunha Cardoso; Carolina Sales Vieira; Elaine Christine Dantas Moisés; Ricardo Carvalho Cavalli (BMC, 2023)
Abstract Background Obesity is a highly prevalent chronic disease that is associated with the development of other metabolic comorbidities. Its etiology is complex and multiple risk factors have been reported. In women, weight gain during pregnancy and the effect of pregnancy on subsequent weight gain are important events in women's history. Both pregnancy and postpartum are critical periods for the development of obesity. Objectives To identify sociodemographic and reproductive risk factors associated with obesity in women in their fourth decade of life. Methods Cohort study conducted on women born from June 1978 to May 1979 in Ribeirão Preto, Brazil. Sociodemographic, clinical, and obstetric data were collected by interview and clinical evaluation. Univariable and multivariable binomial logistic regression models were constructed to identify the risk factors of obesity and the adjusted relative risk (RR) was calculated. Results The cohort included 916 women and 309 (33.7%) of them were obese. Obesity was associated with low educational level (RR 1.77, 95%CI 1.33-2.35) and teenage pregnancy (RR 1.46, 95%CI 1.10-1.93). There was no association of obesity with the other covariates studied. Conclusion Obesity is associated with years of schooling and teenage pregnancy.